Long-lasting economic effects of pandemics: Evidence on growth and unemployment - C. Vladimir Rodríguez-Caballero; J. Eduardo Vera-Valdés (Econometrics, 2020)
This paper studies long economic series to assess the long-lasting effects of pandemics. We analyze if periods that cover pandemics have a change in trend and persistence in growth, and in level and persistence in unemployment. We find that there is an upward trend in the persistence level of growth across centuries. In particular, shocks originated by pandemics in recent times seem to have a permanent effect on growth. Moreover, our results show that the unemployment rate increases and becomes more persistent after a pandemic. In this regard, our findings support the design and implementation of timely counter-cyclical policies to soften the shock of the pandemic.
Keywords: C22; C50; E66; N10; 330; growth; long memory; pandemics; persistence; structural change; unemployment